Prevalence of Common Driver Mutations in Advanced Adenocarcinoma of Lung in a Tertiary Hospital of Nepal - Shilpakar, Ramila; Gurung, Jasmine; Paudel, Saugat; Chapagain, Sandhya; Thapa, Pradip; Pandey, Shama; Acharya, Bibek (Journal of College of Medical Sciences-Nepal, 2021)
Background Molecular testing of lung adenocarcinoma has become standard in clinical practice because the studies have shown that the use of targeted therapies increases the overall survival and quality of life in these patients. The primary aim of this study is to see the prevalence of common driver gene mutations (DGM) in advanced adenocarcinoma of lung in Nepalese population. Methods Retrospective collection of information regarding age, gender, and DGM in advanced lung adenocarcinoma was gathered covering the period from January 2022 to July 2023. Data was analyzed by using SPSS-20 using descriptive statistical tools in terms of frequency and percentage. Results Among 112 patients, 25% had Epidermal Growth Factor Receptor (EGFR) mutation, with exon 19 deletion being more prevalent (17 patients) compared to exon 21 L858R point mutation (nine patients). The occurrence of EGFR mutation was higher in males (14.29%) than in females (10.71%). Anaplastic Lymphoma Kinase (ALK)translocation was identified in six patients, while only one patient exhibited ROS1 rearrangement. Approximately 3% of patients did not undergo successful DGM tests due to insufficient tissue in the biopsy sample. Conclusions A quarter of patients diagnosed with advanced lung adenocarcinoma carry EGFR mutations. Sufficient tissue sampling is necessary to conduct driver mutation tests effectively.